SRATEGI PEMASARAN USAHA MIKRO KECIL MENENGAH AYAM GEPREK BAROKAH BUJUNG BURING MESUJI - M. Amin Fatulloh Fatulloh (Journal Khafi : Journal Of Islamic Studies, 2024)
This study was conducted at the Ayam Geprek Barokah Micro, Small and Medium Enterprises (UMKM) in Buung Buring Village, Tanjung Raya Mesuji Regency. The aim of this research is to study the factors that support and hinder the marketing mix. The purpose of this research is to see how to use the marketing mix in Ayam Geprek Barokah micro, small and medium enterprises (MSMEs). This study uses a qualitative approach. The research subjects were the owners, employees and customers of Ayam Geprek Barokah MSMEs. This research collects data through observation, documentation and interviews. Data analysis includes collection, reduction, delivery, display of categories, and verification of results. The results of this research show that product innovation, pricing, choice of promotional media, and sales location are all important factors that shape marketing strategy.